From Formal Recognition to Effective Access: Regulatory Gaps in the Driving Rights of Persons with Disabilities in Indonesia - Hadi, Ajeng Zatalini Alfiyah; Fadli, Moh.; Hadiyantina, Shinta (International Journal of Business, Law, and Education, 2026)
The right to drive for persons with disabilities is not merely an administrative entitlement attached to a driver’s license; it is a practical component of the right to mobility, independent living, and equal participation. Indonesia has formally recognized this right through the Convention on the Rights of Persons with Disabilities (CRPD), Law No. 8 of 2016 on Persons with Disabilities, and Law No. 22 of 2009 on Road Traffic and Transportation, including the recognition of Class D and D1 driving licenses. Nevertheless, formal recognition has not been matched by operational norms that enable the right to be exercised safely and equally. This article analyzes the regulatory gaps surrounding the driving rights of persons with disabilities in Indonesia through the lenses of Amartya Sen’s capability approach to justice and the doctrine of legal certainty. Using normative legal research with statutory, conceptual, and comparative-supportive approaches, the study examines Indonesian legislation, implementing regulations, international human rights instruments, and relevant legal scholarship. The findings show that the central problem is not the absence of recognition but the incompleteness of implementation: Indonesia lacks comprehensive national standards for adaptive vehicles, disability-responsive driver’s license procedures, and inclusive road-safety mechanisms. These gaps produce legal uncertainty, procedural inequality, and capability deprivation by limiting the real freedom of persons with disabilities to drive independently, safely, and with dignity. The article argues that regulatory reform should shift from declaratory recognition toward enforceable technical standards, functional competence-based licensing, and disability-inclusive safety governance.